A Study of Problem Based Learning and Mathematics Process Skills in Elementary School - Kamid Kamid; Husni Sabil; Wardi Syafmen; Elza Triani (Jurnal Ilmiah Sekolah Dasar, 2021)
The learning process is inseparable from the learning model, the selection of a good learning model will certainly have a good effect on student responses and student process skills and vice versa. This study aims to determine the comparison of student process skills and student responses to the PBL learning model in SD/MI, and to determine the relationship between student responses to student responses to the PBL learning model and student process skills. This type of research is experimental quantitative research by comparing 4 classes using the PBL model. The sample in this study was 144 students from public elementary schools. There are 2 instruments in this research, namely Process Skills for Science and Problem Based Learning (PBL) models. There are 47 items of process skills questions and 26 items of questions in the learning model that uses a Likert scale 5. This study uses quantitative data analysis with the help of SPSS statistics 25, to find descriptive statistics and inferential statistics. The results of the T test showed that in each school there were differences in process skills and student responses to the PBL learning model. Also, the results from the correlation test in each school showed that students' responses to the PBL learning model had an effect on students' process skills. This can be seen from the value of sig. < 0.05. So, the learning model carried out in each school has an influence on student responses and process skills, and there is a relationship between student responses and process skills.